2006
DOI: 10.1186/1471-2164-7-198
|View full text |Cite
|
Sign up to set email alerts
|

Organization and post-transcriptional processing of focal adhesion kinase gene

Abstract: Background: Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase critical for processes ranging from embryo development to cancer progression. Although isoforms with specific molecular and functional properties have been characterized in rodents and chicken, the organization of FAK gene throughout phylogeny and its potential to generate multiple isoforms are not well understood. Here, we study the phylogeny of FAK, the organization of its gene, and its post-transcriptional processing in rodents and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 88 publications
(134 reference statements)
4
66
0
1
Order By: Relevance
“…Although very few bona fide substrates of FAK have been characterized in intact cells (1), the respective role of FAK catalytic activity and scaffolding properties will have to be determined in these autophosphorylation-independent functions. Autophosphorylation-independent function of FAK is also supported by the observation that although Tyr-397 is highly conserved in most metazoans, it is not found in Caenorhabditis elegans (21).…”
Section: Spreading and Morphology Are Altered In Faksupporting
confidence: 54%
See 1 more Smart Citation
“…Although very few bona fide substrates of FAK have been characterized in intact cells (1), the respective role of FAK catalytic activity and scaffolding properties will have to be determined in these autophosphorylation-independent functions. Autophosphorylation-independent function of FAK is also supported by the observation that although Tyr-397 is highly conserved in most metazoans, it is not found in Caenorhabditis elegans (21).…”
Section: Spreading and Morphology Are Altered In Faksupporting
confidence: 54%
“…Here, we addressed this question using a mutant mouse deleted of FAK exon 15, which encodes 19 amino acids, including Tyr-397 (21). Our results show that the requirement for FAK autophosphorylation varies during development and demonstrate that the physiological functions of FAK in vivo are achieved through both autophosphorylation-independent and autophosphorylation-dependent mechanisms.…”
Section: Focal Adhesion Kinase (Fak)mentioning
confidence: 97%
“…These results reinforce the evolutionary conservation of this unique and important Pyk2-FAK survival pathway not shared by other FERM-containing proteins such as talin. Additionally, this survival pathway is independent of integrin regulation (33), as it requires FERM domain function that through evolution has maintained a high level of conservation (34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, alternative FAK transcripts (containing exon 18a) with a premature stop codon have been detected in human brain corresponding to a putative FAK protein encompassing the FAK FERM domain (34). However, cellular and environmental context may dictate whether FAK or Pyk2 FERM domains function in a positive or negative fashion.…”
Section: In Both Fakmentioning
confidence: 99%
“…Therefore, PYK2 expression has been shown to compensate for some functions, although not all, of FAK in cells derived from FAK knockout mice (41). In addition, it has been reported that FAK is subjected to alternative splicing of several coding or noncoding exons that are likely to have important biological functions (39). These data could explain, due to some compensatory mechanism, why the effect of FAK depletion on viral protein expression is not stronger.…”
Section: Discussionmentioning
confidence: 75%